2020
DOI: 10.1111/apa.15464
|View full text |Cite
|
Sign up to set email alerts
|

Using different definitions affected the reported prevalence of neurodevelopmental impairment in children born very preterm

Abstract: Aim We investigated the impact of varying definitions on the prevalence of neurodevelopmental impairment (NDI) in children born very preterm at 6.5 years of age. Methods Cognitive development and neurosensory impairments were assessed in 91 children (40/51 girls/boys) born <32 gestational weeks, in 2004‐2007 in Uppsala county, Sweden. The results were compared with data from a reference group of 67 children born full term. The prevalence of NDI in the present cohort was reported according to definitions used b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(63 reference statements)
2
0
0
Order By: Relevance
“…Comparisons with other populations are difficult due to variability in definitions in ophthalmological outcomes and the large age span in the present study. 23 However, the conclusion that infants born extremely immature are especially vulnerable to ophthalmological and neurological injury is in line with previous studies. 1 5 8 10 In EXPRESS, including infants born before 27 weeks GA and full-term infants in Sweden, Hellgren et al reported strabismus at 6 years of age in 17.4% versus none, and spectacles wear in 36.4% versus 5.7%, respectively, as compared with in our study of children born before 24 weeks GA where we found strabismus were found in 34.8%, and 51.0% had been prescribed spectacles.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Comparisons with other populations are difficult due to variability in definitions in ophthalmological outcomes and the large age span in the present study. 23 However, the conclusion that infants born extremely immature are especially vulnerable to ophthalmological and neurological injury is in line with previous studies. 1 5 8 10 In EXPRESS, including infants born before 27 weeks GA and full-term infants in Sweden, Hellgren et al reported strabismus at 6 years of age in 17.4% versus none, and spectacles wear in 36.4% versus 5.7%, respectively, as compared with in our study of children born before 24 weeks GA where we found strabismus were found in 34.8%, and 51.0% had been prescribed spectacles.…”
Section: Discussionsupporting
confidence: 86%
“…Visual impairment was found in 21.9% and most of the children had ocular and/or visual problems requiring ophthalmological follow-up. Comparisons with other populations are difficult due to variability in definitions in ophthalmological outcomes and the large age span in the present study 23. However, the conclusion that infants born extremely immature are especially vulnerable to ophthalmological and neurological injury is in line with previous studies 1 5 8 10.…”
Section: Discussionsupporting
confidence: 79%